2022
DOI: 10.1111/ane.13715
|View full text |Cite
|
Sign up to set email alerts
|

Advances in sudden unexpected death in epilepsy

Abstract: Sudden unexpected death in epilepsy (SUDEP) is the major cause of premature death in epilepsy patients, particularly those with refractory epilepsy. Sudden unexpected death in epilepsy is thought to be related to peri‐ictal cardiac dysfunction, respiratory depression, and autonomic dysfunction, albeit the exact etiology is unknown. Sudden unexpected death in epilepsy prevention remains a huge challenge. The sole presence and frequency of generalized tonic–clonic seizures (GTCS) are the most important risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…Death, particularly Sudden unexpected death in epilepsy (SUDEP), seems to be the leading cause of premature death in people affected by epilepsy, especially in those patients with refractory epilepsy, and its exact etiology is not known. However, research in animal models revealed that multiple neurotransmitters, including serotonin (5-HT) and adenosine, both of which are targets of CBD biological activity, may be involved in the pathophysiological mechanisms of SUDEP (Zhao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Death, particularly Sudden unexpected death in epilepsy (SUDEP), seems to be the leading cause of premature death in people affected by epilepsy, especially in those patients with refractory epilepsy, and its exact etiology is not known. However, research in animal models revealed that multiple neurotransmitters, including serotonin (5-HT) and adenosine, both of which are targets of CBD biological activity, may be involved in the pathophysiological mechanisms of SUDEP (Zhao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of generalized tonic-clonic seizures (GTCS) is considered the most important clinical risk factor for SUDEP ( 3 , 6 8 ): the higher the GTCS frequency, the higher the risk of SUDEP. Data from a pooled analysis of SUDEP risk factors indicate that patients who have one to two GTCS per year are nearly three times as likely to experience SUDEP than patients who do not have GTCS; patients who have more than 50 GTCS per year are more than 14 times as likely to experience SUDEP ( 8 ).…”
Section: Sudep Risk Factorsmentioning
confidence: 99%
“…In a large Chinese community cohort of 1,562 epileptic patients, 15 experienced suspected SUDEP during the 5-year follow-up period; SUDEP incidence was 2.34 per 1,000 person-years (2). Sudden epileptic death is believed to be related to cardiac dysfunction, respiratory depression, autonomic nervous dysfunction, and brain dysfunction during seizure; however, the exact mechanism is unclear (3)(4)(5). The purpose of this review is to summarize the current knowledge regarding mechanisms of SUDEP.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of sudden death in individuals with epilepsy is 20 times higher than in the general population 1 . Sudden unexpected death in epilepsy (SUDEP) is the most common epilepsy‐related cause of death in persons with epilepsy (PWEs) 2 . The overall risk is around 1 per 1000 person‐years, although this risk substantially increases in PWEs with frequent generalized or focal to bilateral tonic–clonic seizures (TCS) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Sudden unexpected death in epilepsy (SUDEP) is the most common epilepsy‐related cause of death in persons with epilepsy (PWEs) 2 . The overall risk is around 1 per 1000 person‐years, although this risk substantially increases in PWEs with frequent generalized or focal to bilateral tonic–clonic seizures (TCS) 2 . Compared to other neurological conditions, SUDEP is the second leading cause of total years of potential life loss after stroke 3 …”
Section: Introductionmentioning
confidence: 99%